Information and Vaccine Hesitancy: The Role of Broadband Internet - Sofia Amaral-Garcia; Mattia Nardotto; Carol Propper; Tommaso Valletti (Center for Economic Studies and ifo Institute (CESifo), 2024)
We examine the effect of internet diffusion on the uptake of an important public health intervention: the measles, mumps and rubella (MMR) vaccine. We study England between 2000 and 2011 when internet diffusion spread rapidly and there was a high profile medical article (falsely) linking the MMR vaccine to autism. OLS estimates suggest internet diffusion led to an increase in vaccination rates. This result is reversed after allowing for endogeneity of internet access. The effect of internet diffusion is sizable. A one standard deviation increase in internet penetration led to around a 20% decrease in vaccination rates. Localities characterised by higher proportions of high skilled individuals and lower deprivation levels had a larger response to internet diffusion. These findings are consistent with higher skilled and less deprived parents responding faster to false information that the vaccine could lead to autism.
Keywords: D80; I12; L82; L86; 330; vaccines; vaccine hesitancy; internet